PENGEMBANGAN EKONOMI KREATIF MELALUI USAHA INDUSTRI KERIPIK TALAS DENGAN VARIAN RASA DI DESA SUMBER PINANG KECAMATAN MLANDINGAN - Dyan Yuliana; Arico Ayani Suparto; Nur Azizah; Agusti (Bajang Institute, 2022)
The Indonesian government is actively encouraging the creative industry to become an agent of development in improving the country's economy. The creative industry plays an important role in the economy of a country. The main resource of the creative industry is the utilization of individual creativity, skills and talents to create prosperity and employment by generating and exploiting the creative power and creativity of the individual. This service activity aims to help the creative economy community group in Sumber Pinang Village in processing taro into taro chips with original flavors, balado, and sweet corn which are healthy and delicious to eat. The three flavor variants have a distinctive and spicy taste and are very popular for the people of Situbondo, especially in the Mlandingan District. Processing of taro chips with flavor variants has so far never been produced around Sumber Pinang Village, Mlandingan District. The method of implementing this activity is through socialization or counseling, training, product demonstrations, and mentoring, so that the creative economy group in Sumber Pinang Village is able to produce processed taro chips products with flavor variants according to SNI standards. In addition, with this taro chip business, Sumber Pinang Village can have a commercial business scale with high competitiveness and provide high added value for taro processing and increase the income of the local community. The result of this activity is the development of taro chips business with original flavor variants, balado, and sweet corn through business management that is able to improve product quality, quantity, and continuity so as to increase the income of the creative economy group in Sumber Pinang Village. The expected outcome is the development of business management into